STUDY ON THE EFFECT OF METALS CONCENTRATION ON BIOCHEMICAL PARAMETERS IN OREOCHROMIS NILOTICUS OF WARWADE RESERVOIR, DUTSE, JIGAWA STATE-NIGERIA - Samira, I. U.; Nafiu, S. A. (FUDMA Journal of Sciences, 2024)
Warwade water Reservoir and Oreochromis niloticus’s tissues (gills and liver) were evaluated by analyzing heavy metals concentrations and their effects on the oxidative stress enzyme from January to August 2022. Both field and laboratory assessments were conducted following established scientific protocols. Monthly sampling occurred between 6:00 – 7:00 am. Four stations denoted as A, B, C, and D, were chosen based on the diversity of anthropogenic activities surrounding the reservoir. The findings showed that heavy metals concentrations in the water ranked as follows: Chromium at 1.96mg/L, followed by Lead (1.74mg/L), Nickel (1.36mg/L), and Cadmium (1.03mg/L). Heavy metals values in fish tissues exhibited a significant decrease (p<0.05) in the following order for gill tissues (Pb > Cr > Ni > Cd) and liver (Pb > Cr > Cd > Ni). The recorded vlaues exceeded the recommended limits set by WHO (2021). Enzyme activities serving as oxidative stress biomarkers demonstrated a significant reduction (P<0.05) for Superoxide dismutase (SOD), Catalase (CAT) and Glutathione Transferase (GST), with higher mean activity observed in the gills with SOD (16.57 ±0.43), CAT (23.61±2.11) and GST (84.40±1.03) compared to liver samples of GST (81.10±0.51), SOD (14.32 ±1.08) and CAT (20.51±0.17) respectively. It may be inferred that the presence of metals in Oreochromis niloticus is a consequence of the discharge of pollutants into the water body, attributable to urbanization and the discharge of agrochemicals, which adversely impacted the water quality. Consequently, it is imperative to regulate uncontrolled discharges from human activities within the reservoir to mitigate the long-term degradation...